Estudio de factibilidad para la creación de una empresa de asesoría y acompañamiento para la exportación de calzado y marroquinería a los industriales en la ciudad de Pereira, Risaralda (2013)
The following project aims to develop the necessary studies that lead to the creation of a company specialized in providing foreign trade consultants to all small and medium-sized entrepreneurs of footwear and leather goods in the city of Pereira, in order for them to have the necessary support to ensure that these companies will internationalize. All the information that has been collected and processed is registered in this report. It corresponds to the stages of the study of market, operational, administrative, financial and economic.. This ultimately will allow to establish the feasibility of creating the company in the city of Pereira Risaralda, to support the entrepreneur in the process of internationalization of your company. Research is carried out through fieldwork that establish trends for making decisions, in addition to make use of all the tools as texts, brochures, reports, books, statistics, written documents of research undertaken in this regard, among others, that they can contribute to the proper conduct of the investigation. The business idea arises due to entrepreneur’s needs that have the aim to grow and remain in the market and who also seek new alternatives to be recognized and what is better than give them the opportunity to be recognized in foreign markets, besides entering this market provides much more income. In the project we could demonstrate the acceptability of a company with these features in the city of Pereira - Risaralda, but financially the project is not feasible, since It showed a few negative aspects over investment which may affect the company functioning, therefore investment is not recommended.